Application of artificial intelligence in conflict resolution - España Toro, Angie Paola (DIXI, 2024)
Alternative dispute resolution mechanisms (ADRS) and new technologies have emerged as a trending topic, aiming for procedural expediency through novel application methods, including artificial intelligence (AI). AI is a technology based on a set of cognitive and intellectual capabilities expressed through algorithms and computer systems, designed to mimic human intelligence, with the purpose of executing tasks as requested. On the other hand, adrs offer various tools for conflict resolution without the need to resort to judicial offices.
Keywords: Procedural expediency; artificial intelligence; alternative dispute resolution mechanisms; online dispute resolution solutions